On the Translation into French, by Alexandre Zotos of the two Songs from Kreshniks Cycle, â€œAjkuna cries for Omerâ€ and â€œGjergj Elez Aliaâ€ - Isufaj, Drita (Richtmann Publishing, 2012)
Translation of epic poetry is one of themes that causes debates among scholars in the field of translation. This is because ofthe limitations and difficulties that the epic presents. The study will examine the French translation of the epic texts of two of the mostsignificant songs of heroes (Kreshniks) such as â€œAykoune cries for Omerâ€ and â€œGjergj Elez Aliaâ€, by Alexandre Zotos. To translate anepic song the translator can chose between several methods: direct access to the original text, philological translation, the dominantelement translating, translating the hierarchy of elements of the epic text, cultural displacement, etc. Alexandre Zotos apparently mainlyuses the direct access to the original text The translation of this two songs will be analyzed in linguistic and literary level. Elements suchas lexis, semantics, syntax, keeping the rhythm and meter, tropes and their transformation from one language to another, as well astechnical findings of the translator, will be monitored.